English Teachers’ Tecnological Knowledge and Some Barriers on It: The Basis for Developing TPACK Teaching Model - Muliani, Muliani; Sukarni, Sri; Jumadil, Jumadil (JOLLT Journal of Languages and Language Teaching, 2024)
Along with the dynamic development of technology and the need for technology integration in today's learning, technology has become an important element in educational organizations. programs and applications that have been mastered by teachers, namely PowerPoint, Google Translate, Google Doc, the internet, and all forms of technological offerings can undoubtedly support the blended learning pattern which then becomes a learning necessity. Teachers' content and and pedagogical knowledge must be supported by their technological knowledge. The aim of this research is to conduct qualitative research by means of doing semi-structured interview and checking teachers' daily journals about technologies applied in their teaching and learning processes and also the problems of applying those technologies. It was found that there are some technologies commonly used as the instruments of teaching by those 10 teachers in their teaching and learning processes after the pandemic such as: Google Meet, Google Classroom, and WA Group. Next to that, it was also found that there are some common barriers experienced by the teachers in the application of those technologies, such as: hardware and software problems, connectivity, financial problem, protection of personal information, technical support, lack of face-to-face interaction, psychological problems, and language barrier. The result if this research is expected that it can be used as the basis to develop appropriate technologies for teaching English for students to support their CK and PK regarding the implementation of TPACK at school.